Adoption of Improved Technologies Among Nagpur Mandarin Growers in Vidarbha - Vinod Anavrat, (Indian Journal of Extension Education, 2015)
Nagpur mandarin (Citrus reticulata Blanco) popularly known as 'Nagpur Orange' has got a Geographical Indication (GI)tag identity. Besides the Vidarbha region of Maharashtra, it is grown in the three districts of Rajasthan and MadhyaPradesh. Being a cash crop, mandarin cultivation in Maharashtra increased upto 1,35,000 ha and occupies top position interms of area. However, the average productivity of 9-10 tons/ha point at the dismal status of Nagpur mandarin industryespecially in Vidarbha. Hence, to ascertain the causes of technology non-adoption leading to low productivity, the studywas undertaken in the Nagpur mandarin growing area of Central India comprising 300 respondents in a stratified randomsampling. The study revealed that, growers with land large holdings were better adopters due to increased scientificorientation and better extension contacts. Overall, the reason of non-adoption differed with the perceived importance oftechnology by the respondents. However, lack of information was one of the major handicaps and the growers need to beequipped with required information for accelerating the improved technology adoption process.